Wild Things - Jaine, Tom (Petits Propos Culinaires, 2024)
The author, with his partner Joyce Molyneux, runs The Carved Angel Restaurant in Dartmouth. Apart from its other, and outstanding, merits, this establishment is distinguished by having the quality and provenance of its supplies of foodstuffs and wines chronicled in detail in Twelve Times a Year (see PPC 8, p 68). This highly personal and agreeable publication also records what Tom Jaine has been reading about food and wine, and gives interesting insights into the development of recipes and the exploits performed in the kitchen. Here, at our invitation, he reflects on the current vogue for using 'wild foods'.